2016
DOI: 10.1080/20469047.2015.1109239
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity light-emitting diodevsfluorescent tubes for intensive phototherapy in neonates

Abstract: Super LED is a safe rescue treatment for severe neonatal hyperbilirubinaemia, and its implementation may reduce the need for exchange transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Seven studies took measures to keep the irradiance similar in the study groups, 3 15 23 24 32 33 37 while two studies kept the distance between the light source and the infant similar. 25 26 27 28 29 31 34 35 36 38…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies took measures to keep the irradiance similar in the study groups, 3 15 23 24 32 33 37 while two studies kept the distance between the light source and the infant similar. 25 26 27 28 29 31 34 35 36 38…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated 41 full-text articles to check for eligibility, and, ultimately, 21 were included in this review. 3 15 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 The flowchart for evidence search and study selection is shown in Fig. 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations